Recommendations for COVID vaccination for dermatological patients on immunosuppressive/immunomodulatory therapy (IADVL Academy) - Malathi Munisamy; Bhabani S. T. P. Singh; Deepika Pandhi (Wolters Kluwer Medknow Publications, 2021)
Significant proportion of patients with dermatological disorders are on immunosuppressive or immunomodulatory therapy predisposing them to risk of acquisition of COVID-19 infection. However, the efficacy of COVID-19 vaccination among these patients is a matter of concern due to lack of adequate evidence for their protective effect owing to the drug induced immunosuppressed state. Hence, we from the IADVL academy have framed the recommendations to be followed for COVID-19 vaccination among dermatological patients on immunosuppressive therapy based on available related literature.